Challenges and Opportunities for Preserving National Culture in the Digital Age - Abdullayev, Alisher; Almardonov, Azizbek (Journal of Innovation in Education and Social Research, 2025)
The digital age has brought about significant transformations in various aspects of society, including the preservation and dissemination of national culture. While digital technologies offer unprecedented opportunities for cultural exchange and documentation, they also pose challenges that threaten the integrity and authenticity of cultural heritage. This paper examines the multifaceted challenges and opportunities associated with preserving national culture in the digital era. It explores issues such as cultural homogenization, the role of digital technologies in cultural preservation, and the impact of globalization on cultural identities. The paper also discusses strategies for leveraging digital tools to safeguard and promote national culture, emphasizing the importance of a balanced approach that integrates traditional practices with modern technologies.